Public health impact of COVID-19 in French ambulatory patients with at least one risk factor for severe disease - Aurélie Millier; Romain Supiot; Kelly Benyounes; Valérie Machuron; Katell Le Lay; Marine Sivignon; Claire Leboucher; Cécile Blein; François Raffi (Journal of Market Access & Health Policy)
Background Quantification of COVID-19 burden may be useful to support the future allocation of resources.Objective To evaluate the public health impact of COVID-19 in French ambulatory patients with at least one risk factor for severe disease.Study design A Markov model was used to estimate life years, costs, number of hospitalisations, number of deaths and long/prolonged COVID forms over a time horizon of 2 years. The hospitalisation probabilities were derived from an early access cohort, and the hospitalisation stay characteristics were derived from the French national hospital discharge database. Several scenario analyses were conducted.Results The number of hospitalisations reached 256 per 1,000 patients over the acute phase (first month of simulation), and 382 per 1,000 patients over 2 years. The number of deaths was 37 per 1,000 patients, and the number of long/prolonged COVID forms reached 407 per 1,000 patients. These translated into a reduction of 0.7 days of life per patient in the first month, with an associated cost of €1,578, and a reduction of 27 days of life over the time horizon, with an associated cost of €4,280. The highest burden was observed for patients over 80 years old, and those not vaccinated. The scenarios with a less severe situation or new treatments available showed a non-negligible burden reduction.Conclusion This study allowed us to quantify the considerable burden related to COVID-19 in infected patients, with at least one risk factor for severe form. Strategies with the ability to substantially reduce this burden in France are urgently required.